THE INFLUENCE OF ACADEMIC EXPECTATIONS ON MINDFUL PARENTING - Intan Indah Elora Valentina; Setyaningsih (P3I UMSurabaya, 2025)
Madura is an island that forms part of East Java Province, Indonesia. One of its administrative regions, Bangkalan Regency, exhibits a fluctuating pattern of migration each year, both within the country (intercity and inter-regency) and internationally. The region consistently records a significantly negative net migration rate on an annual basis. Parents who migrate and live-apart from their children often entrust their childcare responsibilities to grandparents or other relatives. Children who experience prolonged separation from their parents are more likely to encounter psychological and academic difficulties. Everyparent holds aspirations for their children’s future. Among these aspirations is academic expectation, which refers to parents’ hopes and ambitions regarding their children’s academic achievement and career success. These expectations are often reflected in parents’ child-rearing practices. One effective approach to parenting that can help actualize these expectations is mindful parenting, a parenting style that emphasizes awareness, presence, and conscious attention in guiding children’s development.